Erlendur Haraldsson: An Appreciation - Tucker, Jim (Journal of Scientific Exploration, 2021)
Erlendur Haraldsson, a prolific researcher who made a number of major contributions in various areas of parapsychology and survival research, died in Reykjavik on November 22, 2020 at the age of 89. Born near Reykjavik, Erlendur studied philosophy in college, but his interest in understanding more about the world began before that. When he was 15, he had an experience during a heavy storm when the sun suddenly shone through the clouds and lit up pebbles on the banks of the nearby shore. As the light reflected off the pebbles, Erlendur sensed being filled with light himself in a way that was immense and beyond words. In an interview with Michael Tymn (2015), he said that a vivid trace of that feeling stayed with him forever and that after that, he never doubted that there was a superior reality. Following college, he worked for three years, mostly as a journalist, before returning to school to study psychology, eventually earning a PhD under Hans Bender in Freiburg. After that, he spent a year working at J. B. Rhine’s parapsychology center in Durham, North Carolina, followed by an internship in clinical psychology at the University of Virginia, where he met Ian Stevenson. He and Stevenson studied an Icelandic medium together, introducing Erlendur to the topic of mediumship which he would return to in subsequent decades. Following his internship, he entered the field with a bang. Karlis Osis, the director of research of the American Society for Psychical Research, invited Erlendur to join him in a large study of deathbed visions. They surveyed hundreds of doctors and nurses in both the United States and India about events they had witnessed in their patients. What resulted was a landmark study, one that exemplified the best the field has to offer—detailed statistical analysis along with compelling individual reports. One striking example involved a two-and-a-half year old boy whose mother had died six months before. The respondent wrote, “He was lying there very quiet. He just sat himself up, and he put his arms out and said, ‘Mama,’ and fell back [dead]” (Osis and Haraldsson, 1977, p. 53). Osis and Haraldsson found that the data did not support known medical or psychological causes of hallucinations. Likewise, the influences of religious or other cultural factors could not be used to explain away the phenomena.